Analisis Keekonomian Pembangunan Pembangkit Listrik Tenaga Surya (PLTS) Atap pada Stasiun Yogyakarta - Darmawan, Arief; Nyoto, Edi; Setyo, Dhina; Raharjanto, Yunanda (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study examines the use of a Hybrid Rooftop Solar Power Plant (HRSP) at Yogyakarta Station as a strategic step towards the utilization of renewable energy. The background of this research is highlighted by the global urgency of global warming and climate change, which have wide-ranging impacts on various aspects of life, including the energy sector. As a tropical country, Indonesia has a significant potential in the use of renewable energy, especially solar energy. Yogyakarta Station, as one of the main railway stations in Indonesia serving thousands of passengers daily, requires a high electricity supply, currently predominantly fueled by fossil fuels from PLN. The use of these fossil fuels contributes to the increase in greenhouse gas emissions, a major cause of global warming.This study focuses on the economic analysis of utilizing a Hybrid Rooftop Solar Power Plant (HRSP) at Yogyakarta Station as a strategic step towards renewable energy. The station, a key element in mass transportation, requires a significant supply of electrical energy, currently mostly derived from fossil fuels, contributing to greenhouse gas emissions. The HRSP is proposed as an environmentally friendly alternative, combining solar energy with other sources for sustainable electricity supply. Although it entails a substantial initial investment, technical and economic analyses indicate economic viability, with a Net Present Cost (NPC) of IDR 2,152,699,000.00 and a Cost of Energy (COE) of IDR 1,071.96. With the solar energy potential in the Special Region of Yogyakarta, implementing HRSP could be an economical and sustainable step to replace fossil energy sources at the railway station.